2012
DOI: 10.1016/j.scitotenv.2012.03.006
|View full text |Cite|
|
Sign up to set email alerts
|

Life cycle assessment perspectives on delivering an infant in the US

Abstract: This study introduces life cycle assessment as a tool to analyze one aspect of sustainability in healthcare: the birth of a baby. The process life cycle assessment case study presented evaluates two common procedures in a hospital, a cesarean section and a vaginal birth. This case study was conducted at Magee-Womens Hospital of the University of Pittsburgh Medical Center, which delivers over 10,000 infants per year. The results show that heating, ventilation, and air conditioning (HVAC), waste disposal, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
109
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 112 publications
(112 citation statements)
references
References 16 publications
3
109
0
Order By: Relevance
“…For example, Campion et al utilized LCA to analyze full surgical procedures, including birth and hysterectomy. The results of the birthing study concluded that production of disposable custom packs, the end-of-life impacts of the disposable custom packs, and energy consumption due to HVAC contributed to the highest environmental impacts for both types of birth (cesarean and vaginal) (Campion et al, 2012). The study of four different hysterectomy procedures showed similar findings.…”
Section: Life Cycle Assessmentmentioning
confidence: 81%
See 3 more Smart Citations
“…For example, Campion et al utilized LCA to analyze full surgical procedures, including birth and hysterectomy. The results of the birthing study concluded that production of disposable custom packs, the end-of-life impacts of the disposable custom packs, and energy consumption due to HVAC contributed to the highest environmental impacts for both types of birth (cesarean and vaginal) (Campion et al, 2012). The study of four different hysterectomy procedures showed similar findings.…”
Section: Life Cycle Assessmentmentioning
confidence: 81%
“…Products within each custom pack were separated, weighed, and categorized according to the constituent materials. Materials used in each product were identified through manufacturing data and previous studies (Campion et al, 2012). The environmental impact from the production, use, and disposal of each custom pack was analyzed using process life cycle assessment (LCA) as described in Section 1.1.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, others have utilized the LCA methodology to investigate hospital procedures, such as hysterectomies and C-sections (Bilec, Landis, Shrake, Thiel, & Woods, 2012;Campion et al, 2012). With regards to the LCAs on medical products, they have shown that reprocessed medical devices are environmentally favorable over disposable medical devices (Hailey et al, 2008;Rutala & Weber, 2001;Shuman & Chenoweth, 2012;Suter et al, 2009).…”
Section: Reducing Environmental Impacts Through Reusementioning
confidence: 99%